The Long-Run Exchange Rate for NOK: A BEER Approach - Geir E. Alstad (Norges Bank, 2010)
This paper investigates a long-run relation for the trade weighted NOK exchange rate. I find that the NOK Trade Weighted Index (TWI) cointegrates with the real oil price, the price differential and the real interest differential. The paper documents a long-run solution for the TWI. The paper's main contribution is that the analysis is based on a test for cointegration that is robust to mixed orders of integration in the data. The estimated long-run relation can be considered a benchmark for the nominal exchange rate. This interpretation allows the model to be used when analysing deviations of the nominal exchange rate from the model consistent level. The model is part of the suit of simple cross check models used when analysing the exchange rate in Norges Bank. I also find that the long-run relation is robust to the recent problems in the financial markets.
hdl:11250/2497443
Keywords: C32; C58; F31; 330; time series models; financial econometrics; foreign exchange